How Price Increases Affect Future Purchases: The Role of Mental Budgeting, Income, and Framing - Homburg, Christian; Koschate, Nicole; Totzek, Dirk (Psychology & Marketing, 2010)
This article suggests that mental budgeting processes provide a further understanding of how and to what degree price increases negatively affect a customer's future purchase behavior in a particular category of expenses. Furthermore, the authors analyze how customer income and different price presentation tactics alter this reaction. Results of two experimental studies using both students and non-students show that customer income attenuates the negative effect of a price increase on the likelihood of a future purchase in a particular expense category. As an underlying mechanism, the influence of customer income on future purchase behavior is partially mediated by the degree to which customers engage in mental budgeting. Moreover, mental budgeting strengthens the negative effect of a price increase on a future purchase in the same category of expenses, whereas it does not alter the effect of a price increase on a future purchase in another category. Finally, the framing of a price increase as a percentage versus in absolute terms leads to a lower likelihood of a future category purchase. © 2009 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2010.rw.fbwiwi.migfk.howpri